Fully automated extraction of high-quality total nucleic acids from FFPE specimens for comprehensive genomic profiling of solid tumors - Kristopher Amirault; Michael Collins; Luca Beker; Brandon Mills; Martina Werner; Jonathan Andreas; Daniel Hartman; Jordan Dargert; Vanessa Process; Sean Cederlund; Thuy Dao; Linnea Menin; et al. (SLAS Technology)
Comprehensive Genomic Profiling (CGP) has emerged as a progressive standard of care for the understanding clinical oncology and treatment of solid tumors (Conroy, Pabla et al. 2021). By identifying actionable mutations through next-generation sequencing of solid tumors CGP enables targeted therapy decisions. Formalin-fixed paraffin-embedded tissues are notoriously difficult samples in respect to reliably extracting high-quality nucleic acids and sufficient genetic material to meet sequencing input requirements. In this work we present an automated solution for upstream sample processing of solid tumors to enable high throughput and scalable CGP workflows by eliminating bottlenecks and enhancing results. The Sonication STAR automated DNA and RNA methods from FFPE Tissues was created as a collaboration between Hamilton Company, Covaris, and Labcorp and it offers the potential reduction in quantity not sufficient (QNS) samples and sequencing performance improvements resulting in a 16 % increase in fully reported tumor profiles for patients. This automated approach offers potential saving in workflow costs, improved efficiency, and a reduction in re-extraction and re-sequencing of tumors.